PENGARUH JIWA KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA CAFE DI KOTA PALEMBANG - Dian Utari; Muhammad Yusrik (P3M STIE Mulia Darma Pratama, 2021)
Success business is usually influenced by many factors, both from the internal and external environment of the company. Factors from the internal environment usually come from within the company's own environment which tends to be controlled. One of the internal factors of business success is the entrepreneurial spirit factor. This study will discuss